Detection Technology of Foamed Mixture Lightweight Soil Embankment Based on Ultrasonic Wave Transmission Method - Shikun Pu; Baoning Hong; Xin Liu; Fenqiang Xu; Hao Shan (Advances in Materials Science and Engineering)
This study attempted to establish a process that uses the ultrasonic wave transmission method to correlate the ultrasonic parameters with the material properties of Foamed Mixture Lightweight Soil (FMLS). The results were then applied for the defect detection of the FMLS embankment. First, the ultrasonic wave velocity (UPV) and amplitude (UPA) of FMLS with different mix proportions were collected continuously from 3rd day to 45th day in the curing age. The relationships between UPV versus FMLS elastic modulus, unconfined compressive strength, and density were calibrated. The variations in the ultrasonic parameters owing to the test distance and crack width were recorded. Then, the laboratory tests were reproduced through numerical simulation approach. Finally, the reliability and accuracy of the proposed detection method for FMLS were proved and validated through on-site tests. The proposed methodology, which is simple, stable, and reliable, was found to be suitable for the quality diagnosis of FMLS embankments after construction and during operation.